2010
DOI: 10.4081/ija.2010.265
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Bayesian Network for the Assessment of Agri-Environmental Measures – The Case Study of the Venice Lagoon Watershed

Abstract: A methodological framework was designed to assess the effectiveness of agri-environmental policy measures adopted by the Veneto Region to reduce diffuse water pollution of agricultural origin. Two already existing methodologies were combined in a new flexible approach for policy assessment: Conceptual Modelling and Bayesian Networks (BNs). The former supported the development of a shared conceptual model (a cognitive map) of the agro-ecosystem of the study area; while the latter allowed the development of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This systematic quantitative literature review quantified the reviewed studies, applied decision support approaches in the management of complex and uncertain systems, and found that most of these reviewed studies applied scenario-based approaches to help decision-makers or modellers understand water-related systems, and answer the question 'what if? ', through evaluating the effectiveness of management measures under exploring different scenarios (e.g., [51,127]). Optimization-based approaches were also applied but less frequently.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…This systematic quantitative literature review quantified the reviewed studies, applied decision support approaches in the management of complex and uncertain systems, and found that most of these reviewed studies applied scenario-based approaches to help decision-makers or modellers understand water-related systems, and answer the question 'what if? ', through evaluating the effectiveness of management measures under exploring different scenarios (e.g., [51,127]). Optimization-based approaches were also applied but less frequently.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Corn, Soy, Winter Wheat) (Table 1I). This information was obtained from both literature (Carpani and Giupponi, 2010) and interviews with experts of Veneto Agricoltura (Bonetto, 2012;Regione Veneto, 2014).…”
Section: N and P Fertilizer Applicationmentioning
confidence: 99%
“…Each node of the BDN represents a system component and has a finite set of mutually exclusive and exhaustive states. The states or conditions of the nodes can be categorical, continuous, or discrete (Carpani and Giupponi, 2010) (Table 1).…”
Section: Bayesian Network Development (Steps 3 To 5)mentioning
confidence: 99%
“…( 1) where the posterior probability of an event A, P(A|B), is obtained by multiplying the prior probability of event A, P(A), with its likelihood P(B|A) normalized dividing by P(B), given that B is true (Castelletti and Soncini-Sessa, 2007;Carpani and Giupponi, 2010;Catenacci and Giupponi, 2013).…”
Section: Bayesian Network Development (Steps 3 To 5)mentioning
confidence: 99%
See 1 more Smart Citation